UPAYA MENINGKATKAN HASIL BELAJAR PKN SISWA MENGGUNAKAN METODE ACTUAL LEARNING DI KELAS V SDN 1231/III DUSUN DALAM TAHUN PELAJARAN 2015/2016 - Jasni Elita (STKIP Pesisir Selatan, 2017)
This study aims to improve student learning outcomes by the method of actual learning in the subject of Islamic religious education in the fourth grade SDN 123 / III Hamlet DalamJenis this research is classroom action research with the research subjects fourth grade students of SDN 123 / III Hamlet In totaling 22 people , The object of this research is the implementation and the results obtained from the application of the actual method of learning. Data collection techniques used were observation and tests. Data analysis technique used is descriptive qualitative and quantitative analysis. The results showed that the implementation of learning with actual learning methods to improve learning outcomes of fourth grade students of SDN 123 / III Hamlet In. Increasing the learning process with the actual method of learning on student activity first cycle of 53.82% increased in the second cycle into 68.18%. and the third cycle into 78.01%. The average value of student learning outcomes obtained in the first cycle of 64.55 increased to 73.64 in the second cycle and the third cycle into 79.55. Students who achieve a value ? 65 on the first cycle as many as 14 people or 63.64%. In the second cycle increased to 17 people, or 72.27%, and the third cycle to 20 people or 100% have been completed in the study. Thus, learning the actual methods of learning on the subjects of Civics can be used in class IV SDN 123 / III Hamlet In.